2003
DOI: 10.1002/pros.10267
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine activates P44 and P42 MAPK in human prostate stromal and smooth muscle cells but not in epithelial cells

Abstract: These results suggest that NE may stimulate the proliferation of non-epithelial prostatic cells, which may be involved in the pathogenesis of BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…A considerable part of prostate tissue consists of stroma, where smooth muscle cells are a major cell type [1] . This idea of a localization of ␣ 1 -adrenergic ERK activation is supported by a previous study, where ERK1/2 expression was observed in isolated cultured human prostatic smooth muscle cells [9] . Interestingly, norepinephrine induced ERK1/2 activation in cultured smooth muscle and stromal cells, but not in cultured epithelial cells in that study [9] .…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…A considerable part of prostate tissue consists of stroma, where smooth muscle cells are a major cell type [1] . This idea of a localization of ␣ 1 -adrenergic ERK activation is supported by a previous study, where ERK1/2 expression was observed in isolated cultured human prostatic smooth muscle cells [9] . Interestingly, norepinephrine induced ERK1/2 activation in cultured smooth muscle and stromal cells, but not in cultured epithelial cells in that study [9] .…”
Section: Discussionsupporting
confidence: 70%
“…This idea of a localization of ␣ 1 -adrenergic ERK activation is supported by a previous study, where ERK1/2 expression was observed in isolated cultured human prostatic smooth muscle cells [9] . Interestingly, norepinephrine induced ERK1/2 activation in cultured smooth muscle and stromal cells, but not in cultured epithelial cells in that study [9] . However, neither the type of adrenoceptor mediating this phosphorylation nor any relevance for intact human prostate tissue were identified.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Thebault et al (2003) showed that a 1 -adrenergic receptor-stimulated signaling in normal prostate cells is preferentially coupled to storeindependent transient receptor potential (TRP) channels, as opposed to store-operated TRP channels in the prostate cancer cell line LNCaP. It should be noted, however, that other investigators found no evidence for functional a 1 -adrenergic receptors in cultured normal prostatic epithelial cells, in line with the apparent absence of these receptors in epithelia of prostatic tissues (Kanagawa et al 2003, Marinese et al 2003. Nevertheless, these investigators suggest that isoform-specific inhibitors of TRP channels may be useful for treating prostate cancer.…”
Section: Chemopreventionmentioning
confidence: 99%